Remote Work Leadership - Илиев, Ивайло (Научни трудове, 2023)
Not a small part of business processes are strongly affected by the changes occurring as a result of digitalization. This article traces the importance of remote work and the increasing opportunities for it. The main goal of the paper is to explore and expose the main changes in leadership behavior caused by digital technologies, as well as to analyze the advantages and challenges they present for organizations. Different conditions require different approach and the issue of leadership in such conditions is reviewed. The factor of communication, as a precondition for leadership behavior in digital environment is considered as well. Data from studies related to the affected topics are presented. Basic opinions related to the new requirements for leaders in a digital environment are also summarized. Data from a research conducted related to the considered aspects are presented and conclusions are drawn.
Keywords: Дистанционна работа; Дигитална комуникация; Дигитално лидерство